Effect of In Situ High-Fidelity Simulation Training on the Emergency management of Pneumonia (INSTEP): a mixed-methods study. (1st March 2018) - Leng, Owain Michael; Rothwell, Charlotte; Buckton, Annamarie; Elmer, Catherine; Illing, Jan; Metcalf, Jane
Abstract : Background: The patient safety agenda has propelled the rise of simulation education, but relatively few evaluations of simulation-based educational interventions have focused on patient outcomes. Objective: To evaluate the impact of an in situ, high-fidelity simulation teaching intervention on the management of community-acquired pneumonia in the ambulatory care unit of a district general hospital. Methods: This study used a mixed-methods approach to evaluate the impact of a programme of 10 in situ high-fidelity simulation education sessions delivered to a total of 10 junior doctors, nine nurses and seven healthcare assistants. Participants were tasked with managing a manikin simulating a patient with pneumonia in real time in a working clinical area. Subsequent structured debrief emphasised key themes from the national guidelines on pneumonia management. The intervention was evaluated through an immediate feedback form, follow-up semistructured interviews by independent qualitative researchers that underwent content analysis and triangulation with audit data on compliance with national pneumonia guidelines before and after the simulation intervention. Results: The in situ simulation intervention was valued by participants both in immediate written feedback and in follow-up semistructured interviews. In these interviews, 17 of 18 participants were able to identify a self-reported change in practice following the simulation intervention. Furthermore, most participants reported observing a change in the clinical practice of their colleagues following the training. Collected audit data did not show a statistically significant change in compliance with the guidelines for the management of pneumonia. Conclusion: This study found evidence of a change in both self-reported and observed clinical practice following a simulation intervention, supporting expert opinion that simulation education can impact clinician behaviours and patient outcomes in complex clinical scenarios. Furthermore, this feasibility study provides a transferrable method to evaluate the real-world impact of simulation education that merits further investigation through an appropriately powered study.